Performance Enhancement and Immunity Profile of Broiler Treated Feed Additive Containing Lactic Acid Bacteria and Ganoderma lucidum - A Sofyan; M Angwar; H Herdian; L Istiqomah; A Febrisiantosa; H Julendra; M H Wibowo; T Untari (Media Peternakan, 2012)
The experiment was conducted to evaluate the influence of feed additive containing lactic acid bacteria (LAB) and Ganoderma lucidum (GL) on body weight gain (BWG), feed efficiency (FE), performance index (PI), antibody titer (AT) against Newcastle disease and histopathology of broilers. Bacteria used were Lactobacillus salivarius and Pediococcus pentosaceus, which were isolated from broiler's intestine. A number of 195 unsexed day old chicks (Cobb strain) were arranged in a completely randomized design and consisted of 5 treatments, each in 3 equal replicates. The treatments were as followed T0: control/without-feed additive, T1: 1% LAB (109 cfu g-1), T2: 1% GL, T3: 1% of LAB 109 cfu g-1 + GL (1:1), T4: commercial antibiotic. Data were analyzed using ANOVA and conti-nued to Duncan's multiple range test. The results showed that T2, T3, T4 treatments significantly improved (P < 0.05) BWG, FE and PI of broilers. Broilers fed T3 had the highest PI, followed by T4, T1, T2 and T0. Broilers fed T3 had the highest AT value followed by T0, T2, T4, and T1. Histopathology profile showed that broiler fed T3 had no lesion on liver and intestine compared to others. The result of this experiment indicated that additive containing 0.25% L. salivarius, 0.25% P. pentosaceus, and 0.5% G. lucidum was able to enhance broiler performance.